China in the World - Wang, Ban (Duke University Press, 2023)
Ban Wang traces the shifting concept of the Chinese state from the late nineteenth century to the present, showing how the Confucian notion of tianxia—“all under heaven”—influences China’s dedication to contributing to and exchanging with a common world.